CONSUMPTION OF BRANDED GOODS DURING COVID 19 LOCKDOWN - Dr. Jyoti Achanta, Ms. Shachi Gupta (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Brand name products are purchased and consumed by people for a variety of reasons. The reasons underlying brand consumption are many say for e.g. at times it is the good experiences with the brand in the past, people want to portray a certain image, loyalty of shoppers for their beloved brands. Desire of people to fit in with a specific status group let it be at school, workplace or in social circles. There are people who sometimes buy brands because they think and believe that the brands will contribute to greater social acceptance. This holds true especially in case of fashion. The focus of the present study is on understanding how the people are fulfilling their day to day requirement of essential goods during this lockdown period. And while buying and consuming their day to day essential goods, whether the brand dimension is attached to it or not. To find out the impact of COVID 19 lockdown on consumption pattern and brand consumption, a small survey was carried out. Descriptive research design was opted to collect data from 62 individuals selected through convenience sampling. Questionnaire was used as a tool to collect data and was distributed via google forms. The findings revealed that if branded goods are not available people are willing to consume the goods which are not branded irrespective of their income level and family size.